Death: The Existential Meaning of The Ultimate Phenomenon, Towards an Aesthetics of Consolation - Russell, Thomas (The Stellenbosch Socratic Journal, 2023)
This paper considers the phenomenon of death as it is existentially relevant to us as existents. It raises the question: how should we live given that one day we will die? I explore how death uniquely shapes our conception of who we are and what we can become as naturally constrained human beings. I argue that we should seek to incorporate death as a meaningful consideration and factor in our daily living if we are to self-actualise. Furthermore, I argue that given the above we find ourselves in need of consolation. I proffer a proto-ontological aesthetics that seeks to show from the first principle of the I-You ontological structure of human existence how we can find consolation in a world besieged by death. I argue that there is a reciprocal relation between being-with-others, death, and self-actualisation. We appreciate being-with-others all the more because of the limitation imposed by death, whilst being-with-others allows us to find consolation in the other in the form of being-with-others-to-the-end. The second part of the essay considers the relationship between being-with-others, death and self-actualisation as applied to aesthetics. A number of aesthetic examples are employed that exemplify the reciprocal nature between death, love, and art. Art helps us to discover and integrate ourselves as a being-with-others: it helps us to form meaningful relationships. Thus, art as a mode of being-with-others provides a way for us to reconcile with death, while the finitude imposed by death moves us to find consolation in art.